2021
DOI: 10.1108/ijhma-10-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in real estate: agency practices in Istanbul

Abstract: Purpose This paper aims to discuss unethical behaviors that small real estate agencies encounter in real estate brokerage practices, the factors that give rise to a trust issue and the potential of legal arrangements for offering a solution. Small real estate agencies, almost the only actor in the real estate brokerage industry until the late twentieth century, still strive to survive despite the globalized market, large corporations increasingly dominating the market, the increasing informality and the real e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Real estate companies, however, also sometimes behave unethically (Markoc and Cizmeci, 2021). Therefore, prevention, monitoring of activities and possible sanctions are necessary on the part of public authorities, which should propose a clear legislative framework (Curran and Schrag, 2000).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Real estate companies, however, also sometimes behave unethically (Markoc and Cizmeci, 2021). Therefore, prevention, monitoring of activities and possible sanctions are necessary on the part of public authorities, which should propose a clear legislative framework (Curran and Schrag, 2000).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…(2008, p. 256) observed that setting up an estate agency was easy in England and Wales because estate agents “require no professional qualifications […] and there are few rules about who can set up such a business”. Similarly, Markoc and Cizmeci (2021) writing about real estate brokerage in Istanbul observed that the profession “can be conducted by anybody willing to do it […] because laws do not define the qualifications and professional competencies that [real estate] agencies should have”.…”
Section: Regulation Of Real Estate Psfsmentioning
confidence: 99%
“…and there are few rules about who can set up such a business". Similarly, Markoc and Cizmeci (2021) writing about real estate brokerage in Istanbul observed that the profession "can be conducted by anybody willing to do it [. .…”
Section: Real Estate Professional Services Firmsmentioning
confidence: 99%
“…Therefore, with no prior prioritisation of the adequate ways of housing such households, the intended development of such urban areas could be headed in jeopardy With income flows not stable for financing homeownership acquisition, the most feasible options for the majority of vulnerable households and new migrants or household entrants is renting. Despite the challenges associated with the rental market, like arbitrary evictions, unethical practices of estate agents (Markoc & Cizmeci, 2021) etc, Rental submarkets are more stable than sales submarkets (Hu, He, & Su, 2022) The potential for urban housing can be unleashed only by a coordinated push across a wide range of policy teams. Notably, across sub-Saharan Africa, several housing policies have been enacted since colonial times, which have reported similar results.…”
Section: Introductionmentioning
confidence: 99%